Implicações translacionais de uma nova ferramenta de detecção de célula: tumorais circulantes no monitoramento do câncer de próstata - Oliveira, Leandro Alves de (2017)
Introduction: prostate cancer (PCa) early diagnosis is essential to boost patients’ life expectance. Although, current biomarkers and diagnosis methods do not present reliable sensibility and specificity, making the diagnosis rather imprecise. Recent methodologies have been using circulating tumor cells (CTCs), not for screening of PCa, but as prognosis indicators, employing a vast array of techniques to capture those cells. However, the search for a new biomarkers or diagnosis methods able to screen, diagnosis, assist in prognosis and in the disease monitoring still one of the major technical and scientific objectives to be achieved. Objective: To present a new biomarker for PCa, the aptamer A4, previous screened in the prostate cancer cell line PC3, using 3DCell SELEX. And to able to detect, by flow cytometry, CTCs in blood samples of PCa patients undergoing various treatment regimen. Material and methods: the study evaluated 34 PCa patients and 16 health controls. Blood samples were collected in EDTA tubes, and after erythrocytes lysis, nucleated cells were incubated with A4 aptamer conjugated with biotin, them the cells were washed and incubated with streptavidin-FITC for later flow cytometer analysis. Percentage of CTCs were compared between patient’s groups and correlated against age, PSA levels, staging and treatment regimen (hormonal blockade, radiotherapy and surgery). Detection limit above 1% of CTCs was considered positive, based on the percentage observed on all of the 16 negative controls. Results: all patients were positively diagnosed independently of therapy time or staging, except for one patient undergoing hormonal blockade therapy, which does not present detectable CTCs. CTCs percentage presented high correlation against age (R=0.75) and with PSA levels (R=0.80) with exponential behavior, although, six patients with high CTCs count presented PSA levels <0.02 ng/mL, and were considered was biochemical errors. Conclusion: Our preliminary results indicated high accuracy (98%) and demonstrate a potential application of this technology for diagnosis and screening, as well as in the monitoring of PCa evolution, which should be better investigated in the risk population.